Thermosensitive and Mucoadhesive Pluronic-Hydroxypropylmethylcellulose Hydrogel Containing the Mini-CD4 M48U1 Is a Promising Efficient Barrier against HIV Diffusion through Macaque Cervicovaginal Mucus - Bouchemal, Kawthar (Antimicrob Agents Chemother, 2015)
To be efficient, vaginal microbicide hydrogels should form a barrier against viral infections and prevent virus spreading through mucus. Multiple particle tracking was used to quantify the mobility of 170-nm fluorescently labeled COOH-modified polystyrene particles (COOH-PS) into thermosensitive hydrogels composed of amphiphilic triblock copolymers with block compositions EO(n)-PO(m)-EO(n) (where EO refers to ethylene oxide and PO to propylene oxide) containing mucoadhesive hydroxypropylmethylcellulose (HPMC). COOH-PS were used to mimic the size and the surface charge of HIV-1. Analysis of COOH-PS trajectories showed that particle mobility was decreased by Pluronic hydrogels in comparison with cynomolgus macaque cervicovaginal mucus and hydroxyethylcellulose hydrogel (HEC; 1.5% by weight [wt%]) used as negative controls. Formulation of the peptide mini-CD4 M48U1 used as an anti-HIV-1 molecule into a mixture of Pluronic F127 (20 wt%) and HPMC (1 wt%) did not affect its anti-HIV-1 activity in comparison with HEC hydrogel. The 50% inhibitory concentration (IC(50)) was 0.53 μg/ml (0.17 μM) for M48U1-HEC and 0.58 μg/ml (0.19 μM) for M48U1-F127-HPMC. The present work suggests that hydrogels composed of F127-HPMC (20/1 wt%, respectively) can be used to create an efficient barrier against particle diffusion in comparison to conventional HEC hydrogels.